2019
DOI: 10.1002/we.2384
|View full text |Cite
|
Sign up to set email alerts
|

Changes in design driving load cases: Operating an upwind turbine with a downwind rotor configuration

Abstract: This work considers the design driving load cases from a full design load basis analysis on an upwind turbine changed into a downwind configuration. The upwind turbine is a commercial class IIIA 2.1‐MW turbine, manufactured by Suzlon. The downwind turbine shows an increase in the normalized tower clearance by 6%, compared with the upwind concept. Removing the blade prebend increases the normalized minimum tower clearance by 17% in the downwind configuration compared with the upwind configuration. The extreme l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 6 publications
(8 reference statements)
1
12
0
Order By: Relevance
“…Additionally, segmented blades and outboard pitching ideas were discussed as a means of overcoming the increased edgewise loads of load-alignment. Wanke et al [12] compared a 2.1 MW three-bladed upwind turbine with the downwind counterparts. It was concluded that downwind configurations have no clear advantage over the original upwind design.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, segmented blades and outboard pitching ideas were discussed as a means of overcoming the increased edgewise loads of load-alignment. Wanke et al [12] compared a 2.1 MW three-bladed upwind turbine with the downwind counterparts. It was concluded that downwind configurations have no clear advantage over the original upwind design.…”
Section: Introductionmentioning
confidence: 99%
“…The present paper mainly focuses on the aerodynamic aspects related to these designs. In [9][10][11][12][13][14], although different simulation tools were utilized, the aerodynamic computations were all based on Blade Element Momentum (BEM) theory. However, classical BEM theory is not suitable for coned rotors, especially with a large cone angle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glasgow et al (1981) measured a significant fatigue load increase in the flapwise bending loads for a downwind configuration compared to an upwind configuration of a 100 kW machine due to the velocity deficit of a truss tower. Zahle et al (2009) predicted a reduction in normal force on the blade of 20 %, due to the rapid fluctuation in the angle of attack as the blade passes through the tower wake. A fatigue load increase of around 20 % for the damage equivalent flapwise blade root bending moment was found by Reiso and Muskulus (2013) when comparing the 5 MW NREL reference turbine in a downwind configuration to the original upwind configuration.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of a full design load basis for a commercial Suzlon class IIIA 2.1MW wind turbine in an upwind configuration and a downwind configuration by Wanke et al (2019) showed, that also the edgewise fatigue load increases significantly, when changing the upwind configuration into a downwind configuration. Only 30% of the fatigue load increase for the edgewise blade root sensor could be associated with the tower shadow effect.…”
Section: Introductionmentioning
confidence: 99%